A new Hemigrammus Gill from upper rio Parana system, Southeastern Brazil (Characiformes : Characidae) - Marinho, Manoela M. F. [UNESP]; Carvalho, Fernando R.; Langeani, Francisco [UNESP]; Tatsumi, FLa Vio L. (Magnolia Press, 2008)
Hemigrammus parana is described from the upper rio Parana system, in the area of influence of the Ilha Solteira reservoir in states of Mato Grosso do Sul, Minas Gerais and São Paulo, southeastern Brazil. The new species differs from all congeners by the combination of the following characters: absence of humeral spot; presence of a roughly triangular or rectangular conspicuous black caudal spot, extending from base to tip of middle caudal-fin rays, its greatest depth at base of caudal-fin rays; and anal-fin rays iii-iv, 18-23.
Keywords: Neotropical region; South America; Rio Grande; Taxonomy